A qualitative evaluation of priority-setting by the Health Benefits Package Advisory Panel in Kenya. Issue 1 (14th November 2022) - Mbau, Rahab; Oliver, Kathryn; Vassall, Anna; Gilson, Lucy; Barasa, Edwine
Abstract: Kenya's Ministry of Health established the Health Benefits Package Advisory Panel (HBPAP) in 2018 to develop a benefits package for universal health coverage. This study evaluated HBPAP's process for developing the benefits package against the normative procedural (acceptable way of doing things) and outcome (acceptable consequences) conditions of an ideal healthcare priority-setting process as outlined in the study's conceptual framework. We conducted a qualitative case study using in-depth interviews with national-level respondents ( n = 20) and document reviews. Data were analysed using a thematic approach. HBPAP's process partially fulfilled the procedural and outcome conditions of the study's evaluative framework. Concerning the procedural conditions, transparency and publicity were partially met and were limited by the lack of publication of HBPAP's report. While HBPAP used explicit and evidence-based priority-setting criteria, challenges included lack of primary data and local cost-effectiveness threshold, weak health information systems, short timelines and political interference. While a wide range of stakeholders were engaged, this was limited by short timelines and inadequate financial resources. Empowerment of non-HBPAP members was limited by their inadequate technical knowledge and experience in priority-setting. Finally, appeals and revisions were limited by short timelines and lack of implementation of the proposed benefits package. Concerning the outcome conditions, stakeholder understanding was limited by the technical nature of the process and short timelines, while stakeholder acceptance and satisfaction were limited by lack of transparency. HBPAP's benefits package was not implemented due to stakeholder interests and opposition. Priority-setting processes for benefits package development in Kenya could be improved by publicizing the outcome of the process, allocating adequate time and financial resources, strengthening health information systems, generating local evidence and enhancing stakeholder awareness and engagement to increase their empowerment, understanding and acceptance of the process. Managing politics and stakeholder interests is key in enhancing the success of priority-setting processes.